ILLEGAL INVESTMENT SANCTIONS BASED ON THE CAPITAL MARKET LAW AND FORMS OF PROTECTION FOR INVESTORS - Dian Kartika; Derry Rijken Irahadi; Willy Raymond (Universitas Muhammadiyah Ponorogo, 2023)
The ever-developing technology currently affects the course of the economy. One of them is characterized by a hot issue regarding investment which is often discussed along with the current financial problems, such as inflation which has increased quite significantly, household consumption expenditure which has also increased which has made some people more aware and aware of the importance of saving for the long term. . Investment is the best way because we can save but can get a sizable profit. However, this is actually used by unscrupulous people to take advantage instead of investment. This discussion aims to further analyze the rise of